My Friend and Colleague Hans Rosling - Akuffo, Hannah (Socialmedicinsk tidskrift, 2018)
Hannah Akuffo first met Hans Rosling when she became manager of the KIRT programme at Karolinska Institutet in 1997. He was then chairman of the KIRT Committee. Their diametrically different tempraments made it difficult to work together to begin with. She being more cautious found Hans a bit too "cocky" for her liking. In this article she recalls the turning point – a conversation that marks the beginning of a friendship and a working relationship where they instead came to complement each other through their differences.